Traces of Clay: Exploring Slave and Migrant Identities in Medieval Swahili Zanzibar - Rødland, Henriette (Cambridge Archaeological Journal, 2025)
Abstract The East African coast has long been recognized as a cosmopolitan region, where different cultures and peoples met and exchanged ideas, goods and knowledge. The culture that developed there from the seventh century ce was shaped by these relations, often referred to under the term Swahili, and many of the coastal residents engaged in Islamic practice, long-distance trade, conspicuous consumption of valued goods, and spoke a common language. This paper investigates the presence of slaves and migrants from the East African interior, through pottery assemblages uncovered at two eleventh- to fifteenth-century ce sites in northern Zanzibar: Tumbatu and Mkokotoni. These are groups of people not usually discussed in relation to medieval Swahili towns, and slavery has been especially difficult to study archaeologically on the coast. Through a material culture of difference, I argue that enslaved and non-elite migrants can be recognized and allow for a fuller understanding of socio-economic and cultural complexity in Swahili towns.
Keywords: Esclavage – Zanzibar

En quête d'autonomie: Un couple de rachetés dans la mission catholique de Bagamoyo, Tanzanie (1890-1920) - Nivière, Adèle (Revue d'histoire contemporaine de l'Afrique, 2025)
Bagamoyo, ville de la côte swahilie en Tanzanie actuelle, a été un point névralgique de la traite des esclaves en Afrique de l’Est du xixe siècle au début du xxe siècle. Dans ce contexte, les missionnaires catholiques ont racheté de nombreux esclaves pour les convertir. Une fois mariés, ces anciens esclaves étaient installés dans des villages chrétiens. Cet article retrace la trajectoire d’un de ces couples, à l’échelle individuelle, à travers l’éclairage des registres paroissiaux. Ces archives se révèlent utiles pour retracer les parcours d’émancipation, en particulier du point de vue de la famille, domaine central de la politique missionnaire. Le jeune couple navigue dès lors, en fonction d’opportunités genrées, entre l’insertion dans une communauté affective et religieuse chrétienne, et les réseaux économiques d’appartenance alternatifs offerts dans les villes de la côte swahilie, en dehors du cadre de la mission.
Keywords: Esclavage – Zanzibar